(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this paper, the effect of sodium cyclamate as a artificial sugar substitute, on the amount of glucose and glycogen in the liver tissue of rats was studied under experimental conditions. When sodium cyclamate was administered orally at a dose of 10 mg/kg/day for 60 days, it was observed that the amount of glycogen in the liver tissue of experimental animals decreased. The results indicate the role of sodium cyclamate, a sugar substitute, in the disturbance of carbohydrate metabolism in liver tissue.